The Malaysian Teacher Standards : a look at the challenges and implications for teacher educators - Goh, Pauline Swee Choo (Educational research for policy and practice, 2012)
Talks of education transformation to improve the quality and outcomes of education in Malaysia culminated in the articulation of standards for teachers. The all new Malaysian Teacher Standards (MTS) launched in 2009 is to establish 'high competency' standards for the teaching profession and to increase the status of teachers in Malaysia. This article briefly describes the standards that concern teachers and teacher educators alike. It is proposed that there are three challenges to the standards system that teacher educators may face. First, on transforming ingrained beliefs, values and biased perceptions of teaching that student teachers bring to the teaching institution. The second centres on the rhetoric-reality gap of the MTS itself, while the third challenge involves the actual training of teachers. Given these three challenges, this article also outlines several avenues for teacher educators to consider as they set out to better understand and re-design teacher education programs in this standards-based era of educational transformation. The discussion of the challenges and the proposed resources to meet the challenges are by no means exhaustive or acts as a conclusion but rather to create awareness for further discussion and analysis of the implications proposed in this article. [Author abstract]